2017
DOI: 10.3389/fneur.2017.00394
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Characteristic Motor Patterns Preceding Freezing of Gait in Parkinson’s Disease Using Wearable Sensors

Abstract: Freezing of gait (FOG) is a disabling symptom that is common among patients with advanced Parkinson’s disease (PD). External cues such as rhythmic auditory stimulation can help PD patients experiencing freezing to resume walking. Wearable systems for automatic freezing detection have been recently developed. However, these systems detect a FOG episode after it has happened. Instead, in this study, a new approach for the prediction of FOG (before it actually happens) is presented. Prediction of FOG might enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 43 publications
4
82
0
Order By: Relevance
“…In order for this online cueing modality to work, a “pre‐freezing phase” needs to be characterized reliably. A few studies have investigated the presence of a pre‐FOG phase in the laboratory using different apporaches, including motion analysis systems, surface EMG, electrocardiography, and, more recently, with mobile imaging such as ambulatory EEG, functional near‐infrared spectroscopy, and wearable inertial sensors . Nieuwboer and colleagues found signs of deterioration of the gait pattern as early as three steps before a FOG episode, reflected by a decreased stride length and increased or stable cadence .…”
Section: Assessing the Presence And Severity Of Fog With Wearable Senmentioning
confidence: 99%
See 1 more Smart Citation
“…In order for this online cueing modality to work, a “pre‐freezing phase” needs to be characterized reliably. A few studies have investigated the presence of a pre‐FOG phase in the laboratory using different apporaches, including motion analysis systems, surface EMG, electrocardiography, and, more recently, with mobile imaging such as ambulatory EEG, functional near‐infrared spectroscopy, and wearable inertial sensors . Nieuwboer and colleagues found signs of deterioration of the gait pattern as early as three steps before a FOG episode, reflected by a decreased stride length and increased or stable cadence .…”
Section: Assessing the Presence And Severity Of Fog With Wearable Senmentioning
confidence: 99%
“…Only few reports have characterized the pre‐FOG phase with inertial sensors . The results were promising, particularly in a study of 11 subjects with PD and FOG where information was combined from accelerometers and gyroscopes.…”
Section: Assessing the Presence And Severity Of Fog With Wearable Senmentioning
confidence: 99%
“…Abrupt change points and their locations were then searched in θ z (t) using a predefined Matlab ® function based on the minimisation of a linear computational cost function [50]. Resting breaks were automatically detected by checking in 2-s window increments if: (i) the norm of the lumbar IMU angular velocity was less than 0.5 rad/s; (ii) the norm of the lumbar IMU acceleration was within ±10% of 9.81 m/s 2 [51]. A 2-s window was considered motionless if more than 50% of its samples fulfilled both criteria mentioned above.…”
Section: Data Processingmentioning
confidence: 99%
“…Abbreviations FOG = freezing of gait; DBS = deep brain stimulation; STN = subthalamic nucleus; TBC = Turning and Barrier Course; FW = forward walking; Inertial Measurement Unit = IMU; FOG-Q = Freezing of Gait Questionnaire; LOOCV = leave-one-out cross validation; AUROC = Area Under Receiver Operator Curve; UPDRS = Unified Parkinson's Disease Rating Scale assessments, and clinic-based measurements (Barthel et al, 2016). The authors concluded that there is no "unique methodological tool that encompasses the entire complexity of FOG" and "further development of such an assessment tool requires understanding and thorough analysis of the specific FOG characteristics" (Barthel et al, 2016).Several studies have employed wearable inertial sensors in a variety of different tasks, such as turning 360 degrees in place for two minutes, walking around cones, or walking during dual tasking, to monitor, detect and predict FOG (Coste et al, 2014;Khemani et al, 2015;Kim et al, 2015;Kwon et al, 2014;Palmerini et al, 2017;Rezvanian and Lockhart, 2016;Silva de Lima et al, 2017;Zach et al, 2015). These tasks have improved the detection resolution of FOG but are either not representative of real-world environments or still require a clinical rater to detect freezing episodes, and cannot objectively measure gait impairment, such as arrhythmicity, that is correlated with FOG (Anidi et al, 2018;Hausdorff, 2009;Nantel et al, 2011;Plotnik and Hausdorff, 2008;Syrkin-Nikolau et al, 2017).…”
mentioning
confidence: 99%
“…Several studies have employed wearable inertial sensors in a variety of different tasks, such as turning 360 degrees in place for two minutes, walking around cones, or walking during dual tasking, to monitor, detect and predict FOG (Coste et al, 2014;Khemani et al, 2015;Kim et al, 2015;Kwon et al, 2014;Palmerini et al, 2017;Rezvanian and Lockhart, 2016;Silva de Lima et al, 2017;Zach et al, 2015). These tasks have improved the detection resolution of FOG but are either not representative of real-world environments or still require a clinical rater to detect freezing episodes, and cannot objectively measure gait impairment, such as arrhythmicity, that is correlated with FOG (Anidi et al, 2018;Hausdorff, 2009;Nantel et al, 2011;Plotnik and Hausdorff, 2008;Syrkin-Nikolau et al, 2017).…”
mentioning
confidence: 99%